Deep Learning for Sea Turtle Classification: A Bibliometric Analysis Using VOSviewer - NurFarahim, Siti; Shabil, Azran; Sabrina Balqis, Nur (Universitas Komputer Indonesia, 2024)
Deep learning in the context of sea turtles constitutes a significant area of exploration within marine science. Consequently, the aim of this study is to perform a bibliometric analysis focusing on the subject of sea turtle deep learning, leveraging mapping analysis through the utilization of VOSviewer software. For this research, we employed a bibliometric and descriptive quantitative approach. The data was acquired by conducting a search on Google Scholar using the keyword